2007
DOI: 10.1038/sj.bjc.6603787
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre phase II study of carboplatin plus pegylated liposomal doxorubicin as first-line chemotherapy for patients with advanced or recurrent endometrial carcinoma: the END-1 study of the MITO (Multicentre Italian Trials in Ovarian Cancer and Gynecologic Malignancies) group

Abstract: Anthracyclines and platinum derivates are active drugs for advanced endometrial carcinoma (AEC), but new schedules with higher efficacy and better tolerability are needed. A phase II study was conducted to describe activity and tolerability of carboplatin (C) þ pegylated liposomal doxorubicin (PLD) in patients with AEC. Patients with chemonaive AEC, PS p2, aged o75 years, with at least one measurable lesion were eligible. Treatment was C (area under curve 5) þ PLD (40 mg m À2 ) on day 1 every 4 weeks, up to si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Pegylated liposomal doxorubicin had been tested in the treatment of advanced and recurrent endometrial cancer in monotherapy, with response rate ranging from 9.5% to 21%, 5,16 and in combination with carboplatin, with response rate ranging from 44% to 58.5%. 17,18 The drug was well tolerated with an exactable toxicity profile mainly characterized by moderate hand-foot syndrome (grade 3/4).…”
Section: Discussionmentioning
confidence: 99%
“…Pegylated liposomal doxorubicin had been tested in the treatment of advanced and recurrent endometrial cancer in monotherapy, with response rate ranging from 9.5% to 21%, 5,16 and in combination with carboplatin, with response rate ranging from 44% to 58.5%. 17,18 The drug was well tolerated with an exactable toxicity profile mainly characterized by moderate hand-foot syndrome (grade 3/4).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of liposomal doxorubicin + carboplatin has shown equal activity as paclitaxel + carboplatin in ovarian cancer [29]. In recurrent or advanced endometrial cancer, two fairly large phase 2 trials found response rates of 44% and 52% with a favorable toxicity profile [30,31].…”
Section: Chemotherapy In Advanced or Recurrent Endometrial Cancermentioning
confidence: 99%
“…268 28 endometrial stroma sarcomas). This might be an attractive alternative regimen for women at risk for neurotoxicity.…”
Section: Disease Sitesmentioning
confidence: 99%